Characteristics of interbody bone graft fusion after transforaminal lumbar interbody fusion according to intervertebral space division - Xu, Songjie; Zang, Lei; Lu, Qian; Zhao, Peng; Wu, Qichao; Chen, Xueming (Frontiers in Surgery, 2022)
Background According to intervertebral space division, the characteristics of interbody bone graft fusion after transforaminal lumbar interbody fusion (TLIF) were assessed via computed tomography (CT) scan to provide a theoretical basis for selecting the bone grafting site of interbody fusion. Methods The medical records of 57 patients with lumbar spinal stenosis and disc herniation treated with TLIF were analysed retrospectively. In total, 57 segments received lumbar interbody fusion. A thin-layer CT scan was performed to evaluate fusion in each zone of the fusion space. Results The fusion rates were 57.89% (n = 33) in the anterior cage zone, 73.68% (n = 42) in the posterior cage zone, 66.67% (n = 38) in the decompression zone, 26.32% (n = 15) in the contralateral decompression zone and 94.74% (n = 54) in the inner cage zone. There were significant differences among the fusion rates of the five zones (P < 0.001). Further pairwise comparison revealed that the fusion rates in the inner cage significantly differed from the anterior and posterior cages and decompression and contralateral decompression zones (P = 0.001, 0.002, 0.001 and 0.001, respectively). Conclusion We think the central cage zone (i.e., inner cage) should be the focus of bone grafting. Although there is small volume of bone graft on the posterior cage zone, the fusion rate is relatively high, only secondary to the inner cage zone. The fusion rate is of the contralateral decompression zone is lower although there is a bone graft.